Field notes contributed by Charles Fuller, fall 1988 - Fuller, Charleset al (1988)
List of birds and locations contributed by Charles Fuller. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1988. Epson - sheet feed